ATTENTION-DEFICIT/HYPERACTIVITY DISORDER DIAGNOSIS AND TREATMENT - Diana Purnamasari Tanoyo (Universitas Udayana, 2013)
Attention-deficit/hyperactivity disorder (ADHD) is the most occur neurobehavioral disorder in children, it is also chronically condition that most influence in school children, and it is a disorder of way of thinking that always find in children. ADHD is signed by decrease of attention ability, included increase of distractibilition, and difficulty to defense the attention; difficulty to stronghold impuls control; over activity and restless of motoric. The certain reason of ADHD is not known yet. But it is said that frontal cortex area, such as frontrosubcortical pathways and frontal cortex area itself, is the main area that theoretically has responbility to ADHD patophysiology. We can use DSM Criteria IV to diagnosis child with ADHD. The prognosis of this disorder mostly good. For these children, they have medicine therapy and behavioral therapy. The most important is education to child’s family about this disorder.